They are not rocks, are words (2019)
Along history, has been said that one of the periods of greatest aesthetic splendor, in terms of the art of letters, was the period during which the human being conceived that existence was based in particular on the tragedy. In addition, we enjoyed of all tragic event, in the depths of existential abyss, an extraordinary grasp transfiguration of ourselves as beings who before being meat and shape, we conceive as verb, word knotting feelings and thoughts to objects, the world and life. This tragic flavor that are in language has a dominant role: reveal that words surprise us due to his accuracy status condition and for their ability to trans-form reality in an imaginative event that requires a real understanding of things. With this decision, we are not ensuring that the language is the tragedy in which a multitude of facts that contradict human joviality shown; what I propose is that the language has, in some part of its structure, tragic features that characterize it because words recorded reality without discriminating good and bad, true and false and nonexistent or existing. In the words, simply an abstraction of everything and it does not indicate that each language is a baleful figuration of reality, but a faculty in which the whole is something real that pre-feels, similarly, both the notion of being as non-being.